Sexual health of very young adolescents in South Western Uganda: a cross-sectional assessment of sexual knowledge and behavior - Elizabeth Kemigisha; Katharine Bruce; Viola N. Nyakato; Gad Ndaruhutse Ruzaaza; Anna B. Ninsiima; Wendo Mlahagwa; Els Leye; Gily Coene; Kristien Michielsen (BMC, 2018)
Abstract Background In most Sub-Saharan African countries, little is known about young adolescents' sexual and reproductive health (SRH). Though some efforts have been made to understand and improve SRH of older adolescents, very young adolescents (VYAs) are often overlooked, and little is known about their sexual knowledge and behaviors. The goal of this study was to describe SRH knowledge, information-seeking, and sexual behavior of VYAs in Uganda. Methods A cross-sectional survey was administered in 33 primary schools in June and July of 2016. Trained interviewers administered surveys to adolescents ages 10-14 regarding SRH knowledge, information-seeking, sexual behavior, and relevant covariates. Continuous variables were summarized as means (SD) or medians (IQR) whereas categorical variables were summarized as proportions (percentages). Results A total of 1096 adolescents were included in this analysis, 81.8% of which were from rural areas, with a median age of 12. Regarding sexually transmitted infections (STIs) knowledge; 95% knew HIV while 37% knew other STIs apart from HIV. Although 47% knew at least one way in which HIV is acquired only 8% knew at least four ways. Regarding contraceptive knowledge, 56% mentioned at least one modern method of preventing pregnancy (condoms, pills, intrauterine devices, implants, or injections). The majority (85%) of VYAs reported accessing SRH information in the media with 35% reporting accessing media with sexual content while 10% vs 22% consulted their father or mother respectively and 31% a school source. At least 7.6% of VYAs had ever had sexual intercourse, 90% of which were not using any protection. Conclusion Comprehensive SRH knowledge was low among VYAs in this study. Media remains an important source of information for SRH for this age group though it may be misused as some adolescents reported accessing sexual content that may be inappropriate. A large proportion of sexually active VYAs reported sexual risky behaviors. This study highlights the need for an accurate and more comprehensive SRH education approach for VYAs in Uganda at an opportune age before the majority engage in sexual behavior.